The Influence of Organizational Slack on Firm Performance Moderated by Managerial Ability - Eduard Ary Binsar Naibaho; Fricilia Hardiata (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study examines the influence of organizational slacks on firm performance with managerial ability as a moderating variable. We divide organizational slack into three categories: available slack (current ratio), recoverable slack (sales, general, and administrative expenses ratio), and potential slack (debt-to-equity ratio). Data envelopment analysis (DEA) measures managerial ability and firm efficiency. We collected secondary data from 678 companies in ASEAN 5, excluding the financial sector, on S&P Capital IQ for the period of 2019-2023. We used a fixed-effect panel data model with purposive sampling. The results show that available slack has a positive effect on Tobin's Q and a negative impact on ROA. Recoverable slack, potential slack, and managerial ability have a negative effect on firm performance. Managerial ability can moderate the relationship between organizational slack and Tobin's Q. Additionally, managerial ability can moderate the relationship between recoverable slack and ROA. In contrast, managerial ability cannot moderate the relationship between available slack and potential slack with ROA.